The voice prominence hypothesis: the interplay of F0 and voice source features in accentuation - Yanushevskaya, Irena (My University, 2013)
This paper explores the interplay of source correlates of accentuation, examining a hypothesis (the Voice Prominence Hypothesis) that different source parameters are involved and may serve as equivalent. It predicts that where accentuation is not marked by pitch salience there will be more extensive changes in other source parameters. This follows our assumption that prosodic entities such as accentuation, focus, declination, etc. involve adjustments to the entire voice source and not simply to F0. Twelve 3-accent sentences of Connemara Irish (declaratives, WH questions and Yes/No questions) were analysed. These are typically produced and transcribed as H* H* H*L. Of particular interest were the second accents: although they are heard as accented, there are no particular pitch excursions that would account for their salience. Inverse filtering and subsequent source parameterisation was carried out to yield measures for a range of source parameters. Results support the voice prominence hypothesis: as predicted, the most striking source adjustments were found in the second accent. Even where there is substantial pitch movement (final accent), parameters other than F0 appear to be contributing to the salience of the accented syllable. The precise source changes associated with accentuation varied across sentence types and within the prosodic phrase.
Interspeech 2013
Keywords: Voice source; Accentuation; Prominence